2020
DOI: 10.1093/gji/ggaa433
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of seismic anisotropy associated with the Cook Strait and Kaikōura earthquake sequences in New Zealand

Abstract: Summary Large earthquakes can diminish and redistribute stress, which can change the stress field in the Earth’s crust. Seismic anisotropy, measured through shear-wave splitting (SWS), is often considered to be an indicator of stress in the crust because the closure of cracks due to differential stress leads to waves polarized parallel to the cracks traveling faster than in the orthogonal direction. We examine spatial and temporal variations in SWS measurements and the Vp/Vs ratio associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 112 publications
1
6
0
Order By: Relevance
“…4). This is consistent with results from Graham et al (2020) who map anisotropy fast-axis orientations over the southern HSZ using measurements of shear-wave splitting from local earthquakes (via splitting tomography). Their results generally show margin-parallel orientations, with a deviation at the southern tip of the North Island that suggests a change in the source of anisotropy.…”
Section: Resultssupporting
confidence: 89%
“…4). This is consistent with results from Graham et al (2020) who map anisotropy fast-axis orientations over the southern HSZ using measurements of shear-wave splitting from local earthquakes (via splitting tomography). Their results generally show margin-parallel orientations, with a deviation at the southern tip of the North Island that suggests a change in the source of anisotropy.…”
Section: Resultssupporting
confidence: 89%
“…Most previous SWS studies in the study area use station averaged (or station dominant) local S-waves splitting parameters to investigate the spatial distributions of anisotropy characteristics, a practice that is incapable of revealing possible raypath dependent splitting parameters associated with the 3-D heterogeneity of crustal anisotropy. Additionally, in areas with strong anisotropy heterogeneities like the study area, the individual splitting parameters observed at a given station may vary as a function of the azimuth and focal depth of the events (Figure 5), as observed by numerous previous studies (e.g., Graham et al, 2020;Zinke & Zoback, 2000). Consequently, the station averaged splitting parameters may be biased toward measurements in the most populous event clusters, possibly resulting in misleading implications of the actual anisotropy structure.…”
Section: Three-dimensional Variations Of Upper Crustal Anisotropymentioning
confidence: 83%
“…The first is stress‐induced anisotropy from preferentially aligned fluid‐filled microcracks that are mostly parallel to the maximum horizontal compressive stress direction (SHmax; Cao et al., 2019; Crampin & Booth, 1985; Crampin, 1987; Piccinini et al., 2006; Yang et al., 2011), and the second is structure‐induced anisotropy that is mostly from fluid‐filled fractures along fault zones (Cochran et al., 2020, 2003; Gao et al., 2019; Li et al., 2014; Zinke & Zoback, 2000), aligned terrane minerals (Okaya et al., 2016), and sedimentary layering (Audet, 2015). While it is a common practice in previous SWS studies to present station‐averaged splitting parameters and interpret the measurements under the assumption that a single anisotropy‐forming process dominates beneath a given station, some studies (e.g., Ando et al., 1980; Audoine et al., 2004; Graham et al., 2020; Zinke & Zoback, 2000) report individual measurements and explore spatial variations of the observed splitting parameters for the purpose of delineating the three‐dimensional (3‐D) distribution of anisotropic properties, a practice that is adopted in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Crustal anisotropy has also been assessed in a variety of tectonic settings using S-waves from local earthquakes [e.g. Crampin, 1990;Graham et al, 2020;Savage et al, 2010;Zal et al, 2020].…”
Section: Shear-wave Splittingmentioning
confidence: 99%
“…Crustal anisotropy using local earthquakes has also been assessed in a variety of tectonic settings [e.g. Crampin, 1990;Graham et al, 2020;Savage et al, 2010;Zal et al, 2020]. Shear-wave splitting has also been used to measure anisotropy with mode-converted phases in controlled-source seismic data, specially PPS phases [e.g.…”
Section: Shear-wave Splittingmentioning
confidence: 99%